Role of decongestants in a complex therapy of acute infectious rhinitis - A. A. Krivopalov; P. A. Shamkina (Медицинский совет, 2020)
Nowadays the problem of treating of acute respiratory viral infections, primarily manifested with the clinical picture of acute rhinitis, remains an important problem due to the high prevalence and variety of etiological factors of this disease. Pathogenesis of rhinitis, regardless of the etiology, includes the swelling of the nasal mucosa, the increase in nasal secretion, which blocks nasal breathing and significantly reduces the quality of life. In uncomplicated forms of acute infectious rhinitis, symptomatic treatment is traditionally used, including the elimination therapy and drugs for reducing the nasal mucosa swelling. Topical decongestants have a sympathomimetic effect, affect α1- and α2-adrenergic receptors and help to eliminate swelling of the nasal mucosa and improve nasal breathing, and as a result, restore the patency and aerodynamics of the airways, recover the drainage function of the paranasal sinuses and auditory tube. To date, the pharmaceutical market offers many intranasal decongestants that differ in the duration of exposure, frequency of use, the occurrence of side effects or adverse events. The article shows the pharmacological and pharmacokinetic characteristics of the drug xylometazoline, highlights the results of Russian and foreign studies that demonstrate the efficacy and good tolerability of xylometazoline with a short-term topical course of treatment. The conclusion is made about a good profile of the efficacy and safety of the drug and confirmed that in compliance with the recommendations for the frequency and duration of application, xylometazoline could be recommended for use in a complex symptomatic treatment of acute rhinitis in adults and children.